Geotechnics and earthquake geotechnics towards global sustainability - Iai, Susumu (Geotechnical, Geological, and Earthquake Engineering, 2011)
This book is part of a bold, new initiative towards global sustainability and development that draws on the disciplines of geotechnical engineering and earthquake geotechnics.  It contains contributions from fifteen of the world's leading experts who met in Kyoto in early 2010 to discuss a range of issues related to the ways geotechnics can help us face the challenges ahead, from the technical to the social, from geo-hazards to megacities, from global warming and coastal protection to the conservation of world heritage sites.    We hope these contributions will stimulate the debate over the role geotechnics has to play in achieving a more sustainable future for the world. Audience This book will be of interest to advanced levels of researchers and practicing engineers in the fields of geotechnics and earthquake geotechnics for global sustainability: the greatest long term challenge of our t